Metal particle / porous active metal oxide composite catalytic material as well as preparation method and application thereof
Nano-metal colloids were prepared by liquid phase pulse laser irradiation technology and implanted with porous oxide matrix using complex precipitation method, which solved the problem of poor stability of Pt-based catalysts at high temperatures, and developed efficient and stable dehydrogenation of non-precious metal propane The catalyst achieves high catalytic activity and stability of propane dehydrogenation reaction.
Patent Information
- Application Number
- CN202411488270.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-17
AI Technical Summary
The existing Pt-propane dehydrogenation catalysts are prone to sintering and growing under high temperature conditions, and the carbon deposits are inactivated, with poor stability, making it difficult to develop and optimize efficient and stable non-precious metal-based catalysts.
Nano-metal colloidal solution was prepared by liquid phase pulse laser irradiation technology, and metal particles were implanted in situ into porous metal oxide matrix by one-step complex precipitation method, and metal particles/porous active metal oxide composite catalytic material was synthesized to achieve The uniform loading and high dispersion of metal particles are achieved.
It improves the stability and catalytic activity of the catalyst, and has high catalytic activity and stability when applied to propane dehydrogenation reaction, which is simple, energy-saving, environmentally friendly, and has broad application prospects.
Smart Images

Figure CN119318962A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermal catalytic materials, and in particular relates to a metal particle / porous active metal oxide composite catalytic material and a preparation method and application thereof. Background Art
[0002] As an important organic chemical raw material, the demand for propylene continues to grow both at home and abroad, and the supply is insufficient and the gap between supply and demand continues to expand. The propane dehydrogenation (PDH) process is a technology that uses propane as a raw material to produce propylene in a targeted manner. It has the advantages of a wide range of raw material sources, high propylene selectivity, and simple and easy product separation, and has attracted much attention. x Base, VO x Base, GaO x Base, ZrO 2 Propane dehydrogenation catalysts such as bisphenol A were studied and reported.
[0003] Al 2 O 3 and CeO 2 Supports are widely used in propane dehydrogenation catalysts due to their large specific surface area, high mechanical strength, good thermal conductivity, high thermal stability and low cost. Pt-based catalysts have high reaction activity, however, Pt particles are prone to sintering and growth under high temperature conditions, and are also prone to carbon deposition and deactivation, and have poor stability. Non-precious metal-based (such as Ni-based, In-based, V-based, Cr-based) catalysts have the advantages of high catalytic CH bond activation activity and low cost, and are an ideal choice to replace Pt-based propane dehydrogenation catalysts. How to develop and optimize efficient and stable non-precious metal-based catalysts is a technical difficulty that technicians in this field need to solve. Summary of the invention
[0004] In view of the deficiencies in the above-mentioned prior art, the present invention provides a metal particle / porous active metal oxide composite catalytic material, a preparation method thereof and an application thereof in propane dehydrogenation. The present invention is based on laser liquid phase manufacturing technology to prepare a variety of nano-metal colloid solutions, and through a one-step complex precipitation method, the metal particles are in situ implanted into a porous metal oxide matrix to synthesize a metal particle / porous metal oxide (including aluminum oxide and cerium oxide, etc.) composite catalytic material.
[0005] To achieve the above purpose, the technical solution specifically adopted by the present invention is as follows:
[0006] A first aspect of the present invention provides a metal particle / porous active metal oxide composite catalytic material, wherein the metal particles are uniformly loaded on the surface and in the matrix of the porous active metal oxide, and the metal particles are in a highly dispersed state.
[0007] The second aspect of the present invention provides a method for preparing a metal particle / porous active metal oxide composite catalytic material, the method comprising the following steps:
[0008] Step 1: preparing a colloidal solution of metal particles by liquid phase pulsed laser irradiation technology;
[0009] Step 2: Under magnetic stirring, dissolving the precursor metal salt for preparing the porous active metal oxide in the metal particle colloidal solution in step 1, adding ammonium carbonate as a precipitant, and uniformly dispersing by ultrasonication to obtain a mixed solution;
[0010] Step 3: placing the mixed solution of step 2 in a constant temperature oven, keeping the temperature, using a complex precipitation method to react ammonium carbonate with metal salt ions to generate a complex precipitate, then centrifugally separating and washing the precipitate, and drying overnight to obtain a solid intermediate product;
[0011] Step 4: Place the solid intermediate product obtained in step 3 into a muffle furnace and perform high-temperature calcination treatment to finally obtain a metal particle / porous active metal oxide composite catalytic material.
[0012] As a further illustration of the present invention, step 1 specifically comprises:
[0013] A metal target is selected, polished and placed in a solvent, the condensation temperature is maintained at -20-0°C, a nanosecond pulse laser beam is used to bombard the metal target, and ultrasonic treatment is performed at the same time. After irradiation for a certain period of time, the metal target is taken out to obtain a metal particle colloidal solution.
[0014] As a further illustration of the present invention, in step 1, the metal target material used in preparing the metal particle colloidal solution is one or more of In, V, Cr, and Ni; and / or the solvent used is ultrapure water, and / or the laser flux of the pulsed laser beam is 600-2000 mJ pulse -1 cm -1 The laser beam irradiates the metal target for 2-15 min.
[0015] As a further illustration of the present invention, the porous metal oxide is one or more of aluminum oxide, cerium oxide, gallium oxide and zirconium oxide; wherein the precursor metal salt is one or more of aluminum nitrate, aluminum sulfate, aluminum chloride, cerium nitrate, cerium sulfate, cerium chloride, gallium nitrate, gallium acetate, gallium chloride, zirconium nitrate, zirconium chloride and zirconium sulfate; the molar ratio of ammonium carbonate to metal salt is 2:1-9:1.
[0016] As a further illustration of the present invention, in step 2, the ratio of the metal salt to the metal particle colloidal solution is 0.02 mol / L to 0.20 mol / L; the time of the magnetic stirring and ultrasonic dispersion treatment is 15 min and 30 min, respectively.
[0017] As a further illustration of the present invention, in step 3, the insulation temperature is 80-180°C, the insulation time is 6-36h, the centrifugal separation is performed at a speed of 7000 r / min for 3 min; when washing the precipitate, it is washed three times with ultrapure water and anhydrous ethanol respectively; and the drying temperature is 60°C.
[0018] The third aspect of the present invention provides the use of the above-mentioned metal particle / porous active metal oxide composite catalytic material or the metal particle / porous active metal oxide composite catalytic material prepared by the above-mentioned method in propane dehydrogenation.
[0019] As a further illustration of the present invention, the metal particle / porous metal oxide composite catalytic material and quartz sand are uniformly mixed and loaded into a fixed bed reactor containing a quartz tube, and a mixed gas of propane, carbon dioxide and argon is introduced in a nitrogen atmosphere to carry out a dehydrogenation reaction.
[0020] Compared with the prior art, the present invention has the following beneficial technical effects:
[0021] (1) The present invention successfully prepared various metal nanoparticles such as Ni, V, In, Cr, etc. based on liquid phase pulsed laser irradiation technology. The size and loading amount of the metal particles can be controlled by adjusting the irradiation time, laser energy and wavelength.
[0022] (2) The present invention uses a complex precipitation method to in-situ implant metal nanoparticles into the surface and matrix of a porous carrier, with uniform loading and without changing the microscopic morphology and structure of the porous carrier. The preparation process is simple, energy-saving, efficient, environmentally friendly, and highly scalable, and has broad application prospects.
[0023] (3) The metal particle / porous metal oxide composite catalytic material prepared by the present invention, thanks to the high specific surface area and thermal stability of the porous metal oxide carrier, provides a large number of stable and exposed active sites for the catalytic reaction. When applied to the propane dehydrogenation reaction, it has high catalytic activity and stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 For Ni@Al in Example 1 2 O 3 TEM images and element distribution diagrams at different magnifications: Figure a is Ni@Al 2 O 3 Figure b is a high-angle annular dark field transmission electron microscopy (HAADFTEM) image and Al, O, and Ni element distribution map. Figure b is a Ni@Al 2 O 3 High-resolution TEM image of .
[0025] Figure 2V@Al in Example 2 2 O 3 TEM images and element distribution diagrams at different magnifications: Figure a is V@Al 2 O 3 Figure b shows the high-angle annular dark field transmission electron microscopy (HAADFTEM) image and the distribution of Al, O, and V elements. Figure b shows V@Al 2 O 3 High-resolution TEM image of .
[0026] Figure 3 Cr@Al in Example 3 2 O 3 TEM images and element distribution diagrams at different magnifications: Figure a is Cr@Al 2 O 3 Figure b is a high-angle annular dark field transmission electron microscopy (HAADFTEM) image and Al, O, and Cr element distribution map. Figure b is a Cr@Al 2 O 3 High-resolution TEM image of .
[0027] Figure 4 In@CeO in Example 4 2 TEM images and element distribution diagrams at different magnifications: Figure a shows In@CeO 2 Figure b shows the high-angle annular dark field transmission electron microscopy (HAADFTEM) image and the distribution of Ce, O, and In elements. Figure b shows In@CeO 2 High-resolution TEM image of .
[0028] Figure 5 For Ni@Al in Examples 1-4 2 O 3 、V@Al 2 O 3 ,Cr@Al 2 O 3 、In@CeO 2 Propane dehydrogenation performance curve. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Pt-based catalysts have high reaction activity. However, Pt particles tend to sinter and grow under high temperature conditions, and are also prone to carbon deposition and deactivation, and have poor stability. Non-precious metal-based (such as Ni-based, In-based, V-based, Cr-based) catalysts have the advantages of high catalytic CH bond activation activity and low cost, and are ideal choices to replace Pt-based propane dehydrogenation catalysts. How to develop and optimize efficient and stable non-precious metal-based catalysts is a technical difficulty that technicians in this field need to solve.
[0031] Based on the solution of the above technical problems, the present invention provides a metal particle / porous active metal oxide composite catalytic material, a preparation method thereof and its application in propane dehydrogenation. The present invention is based on laser liquid phase manufacturing technology to prepare a variety of nano-metal colloid solutions, and through a one-step complex precipitation method, the metal particles are in situ implanted into the porous metal oxide matrix to synthesize a metal particle / porous metal oxide (including aluminum oxide and cerium oxide, etc.) composite catalytic material.
[0032] The method for preparing the metal particle / porous active metal oxide composite catalytic material provided by the present invention comprises the following steps:
[0033] Step 1: Prepare metal particle colloidal solution by liquid phase pulsed laser irradiation technology.
[0034] Step 1 specifically includes: selecting a metal target, putting it into a solvent after polishing, maintaining the condensation temperature at -20-0°C, bombarding the metal target with a nanosecond pulse laser beam, and simultaneously performing ultrasonic treatment, taking out the metal target after irradiation for a certain period of time, and obtaining a colloidal solution of metal particles.
[0035] Furthermore, the metal target material used in preparing the metal particle colloidal solution is one or more of In, V, Cr, and Ni.
[0036] Furthermore, the solvent used was ultrapure water, and the solvent volume was 10 mL.
[0037] Furthermore, the laser flux of the pulsed laser beam is 600-2000 mJ pulse -1 cm -1 , for example, it can be 600mJpulse -1 cm -1 、800mJ pulse -1 cm -1 、1000mJ pulse -1 cm -1 、1200mJ pulse -1 cm -1 、1400mJ pulse - 1 cm -1、1600mJ pulse -1 cm -1 、1800mJ pulse -1 cm -1 、2000mJ pulse -1 cm -1 etc.; the time for the laser beam to irradiate the metal target is 2-15 min, for example, it can be 2 min, 5 min, 10 min, 15 min, etc.
[0038] Step 2: Under magnetic stirring, the precursor metal salt for preparing the porous active metal oxide is dissolved in the metal particle colloidal solution in step 1, and ammonium carbonate is added as a precipitant, and ultrasonic dispersion is performed to obtain a mixed solution.
[0039] Furthermore, the porous metal oxide is one or more of aluminum oxide, cerium oxide, gallium oxide and zirconium oxide.
[0040] Furthermore, the precursor metal salt for preparing the porous metal oxide is one or more of aluminum nitrate, aluminum sulfate, aluminum chloride, cerium nitrate, cerium sulfate, cerium chloride, gallium nitrate, gallium acetate, gallium chloride, zirconium nitrate, zirconium chloride and zirconium sulfate, wherein the ratio of ammonium carbonate to the metal salt is 2:1 to 9:1 (molar ratio), for example, it can be 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, etc.
[0041] Furthermore, the ratio of the metal salt to the metal particle colloidal solution is 0.02 mol / L to 0.20 mol / L, for example, 0.02 mol / L, 0.05 mol / L, 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, etc.
[0042] Furthermore, in step 2, the time for magnetic stirring and ultrasonic dispersion treatment is 15 min and 30 min, respectively.
[0043] Step 3: Place the mixed solution of step 2 in a constant temperature oven for heat preservation, and use the complex precipitation method to react ammonium carbonate with metal salt ions to generate a complex precipitate, then centrifuge and wash the precipitate, and dry it overnight to obtain a solid intermediate product.
[0044] Furthermore, the insulation temperature in step 3 is 80-180°C, for example, it can be 80°C, 100°C, 120°C, 140°C, 160°C, 180°C, etc.; the insulation time is 6-36 h, for example, it can be 6 h, 12 h, 18 h, 24 h, 36 h, etc.
[0045] Furthermore, the centrifugal separation was performed at a speed of 7000 r / min for 3 min.
[0046] Furthermore, the precipitate was washed three times with ultrapure water and anhydrous ethanol respectively; the drying temperature was 60°C.
[0047] Step 4: The solid intermediate product obtained in step 3 is placed in a muffle furnace and subjected to high-temperature calcination treatment to obtain a metal particle / porous metal oxide composite catalytic material.
[0048] Furthermore, in step 4, the calcination temperature is 500-900°C, for example, 500°C, 600°C, 700°C, 800°C, 900°C, etc.; the heating rate is 10°C / min, and the holding time is 3-5 h, for example, 3 h, 4 h, 5 h, etc.
[0049] The metal particle / porous active metal oxide composite catalytic material prepared by the above method can be used in propane dehydrogenation as a high-efficiency catalyst, specifically:
[0050] The metal particles / porous metal oxide composite catalytic material and quartz sand are mixed evenly, loaded into a fixed bed reactor containing a quartz tube, and a mixed gas of propane, carbon dioxide and argon is introduced in a nitrogen atmosphere to carry out a dehydrogenation reaction.
[0051] The technical solution of the present invention is further explained below in conjunction with specific embodiments and comparative examples.
[0052] Example 1
[0053] This embodiment provides a metal Ni particle / porous alumina composite catalytic material (Ni@Al 2 O 3 ), comprising the following steps:
[0054] (1) A polished Ni sheet (2 cm × 2 cm, 2 mm thick) was placed in a glass bottle containing 10 ml of ultrapure water. The glass bottle was fixed in an ultrasonic machine with 0°C water circulation. A laser with a flux of 1.0 mJ pulse was used under continuous ultrasonic conditions. -1 cm -2 The metal Ni sheet was bombarded with a nanosecond pulsed laser beam (Nd:YAG) for 10 min to prepare a Ni metal nanoparticle colloidal solution.
[0055] (2) Aluminum nitrate nonahydrate (Al(NO 3 ) 3 9H 2 O, 3 g) and ammonium carbonate (NH 4 ) 2 CO 3, 6.92 g) was dissolved in 400 mL of the Ni metal nanoparticle colloidal solution of step (1), magnetically stirred for 15 min, and ultrasonically treated for 30 min to obtain a mixed solution.
[0056] (3) The mixed solution of step (2) is placed in a constant temperature oven, heated to 80°C for 6 h, then heated to 180°C for 24 h, cooled to room temperature, and then washed three times with ultrapure water and ethanol respectively, and placed in a drying oven at 60°C for one night to obtain a solid intermediate product.
[0057] (4) The solid intermediate product of step (3) was placed in a muffle furnace, heated to 800°C at a rate of 10°C / min and kept at that temperature for 3 h, and then cooled to room temperature to obtain a metal Ni particle / porous alumina composite catalytic material (Ni@Al 2 O 3 ).
[0058] Example 2
[0059] This embodiment provides a metal V particle / porous alumina composite catalytic material (V@Al 2 O 3 ), comprising the following steps:
[0060] (1) A polished metal V-sheet (2 cm × 2 cm, 2 mm thick) was placed in a glass bottle containing 10 ml of ultrapure water. The glass bottle was fixed in an ultrasonic machine with 0°C water circulation. A laser with a flux of 1.0 mJ pulse was used under continuous ultrasonic conditions. -1 cm -2 The metal V sheet was bombarded with a nanosecond pulsed laser beam (Nd:YAG) for 10 min to prepare a colloidal solution of V metal nanoparticles.
[0061] (2) Aluminum nitrate nonahydrate (Al(NO 3 ) 3 9H 2 O, 3 g) and ammonium carbonate (NH 4 ) 2 CO 3 , 6.92 g) was dissolved in 400 mL of the above solution, magnetically stirred for 15 min, and ultrasonically treated for 30 min to obtain a mixed solution.
[0062] (3) The mixed solution of step (2) is placed in a constant temperature oven, heated to 80°C for 6 h, then heated to 180°C for 24 h, cooled to room temperature, and then washed three times with ultrapure water and ethanol respectively, and placed in a drying oven at 60°C for one night to obtain a solid intermediate product.
[0063] (4) The solid intermediate product of step (3) was placed in a muffle furnace, heated to 800°C at a rate of 10°C / min and kept at that temperature for 3 h, and then cooled to room temperature to obtain a metal V particle / porous alumina composite catalytic material (V@Al 2 O 3 ).
[0064] Example 3
[0065] This embodiment provides a metal Cr particle / porous alumina composite catalytic material (Cr@Al 2 O 3 ), comprising the following steps:
[0066] (1) A polished Cr sheet (2 cm × 2 cm, 2 mm thick) was placed in a glass bottle containing 10 ml of ultrapure water. The glass bottle was fixed in an ultrasonic machine with water circulation at 0 °C. A laser with a flux of 1.0 mJ pulse was used under continuous ultrasonic conditions. -1 cm -2 The metal Cr sheet was bombarded with a nanosecond pulsed laser beam (Nd:YAG) for 10 min to prepare a colloidal solution of V metal nanoparticles.
[0067] (2) Aluminum nitrate nonahydrate (Al(NO 3 ) 3 9H 2 O, 3 g) and ammonium carbonate (NH 4 ) 2 CO 3 , 6.92 g) was dissolved in 400 mL of the above solution, magnetically stirred for 15 min, and ultrasonically treated for 30 min to obtain a mixed solution.
[0068] (3) The mixed solution of step (2) is placed in a constant temperature oven, heated to 80°C for 6 h, then heated to 180°C for 24 h, cooled to room temperature, and then washed three times with ultrapure water and ethanol respectively, and placed in a drying oven at 60°C for one night to obtain a solid intermediate product.
[0069] (4) The solid intermediate product of step (3) was placed in a muffle furnace, heated to 800°C at a rate of 10°C / min and kept at that temperature for 3 h, and then cooled to room temperature to obtain a metal Cr particle / porous alumina composite catalytic material (Cr@Al 2 O 3 ).
[0070] Example 4
[0071] This embodiment provides a metal In particle / porous cerium oxide composite catalytic material (In@CeO 2 ), comprising the following steps:
[0072] (1) A polished metal In sheet (2 cm × 2 cm, 2 mm thick) was placed in a glass bottle containing 10 ml of ultrapure water. The glass bottle was fixed in an ultrasonic machine with 0°C water circulation. A laser with a flux of 1.0 mJ pulse was used under continuous ultrasonic conditions. -1 cm -2 The metal In sheet was bombarded with a nanosecond pulsed laser beam (Nd:YAG) for 10 min to prepare an In metal particle colloidal solution.
[0073] (2) 21.93 g Ce(NH 4 ) 2 (NO 3 ) 6 and 7.69 g (NH 4 ) 2 CO 3 Dissolve in 400 mL of the In metal particle colloidal solution prepared in step (1), stir magnetically for 15 min, and ultrasonically treat for 30 min to obtain a mixed solution.
[0074] (3) The mixed solution of step (2) is placed in a constant temperature oven, heated to 80°C for 6 h, then heated to 180°C for 24 h, cooled to room temperature, and then washed three times with ultrapure water and ethanol respectively, and placed in a drying oven at 60°C for one night to obtain a solid intermediate product.
[0075] (4) The solid intermediate product of step (3) was placed in a muffle furnace and heated to 550°C at a heating rate of 10°C / min and kept at this temperature for 4 h to obtain a metal In particle / porous cerium oxide composite catalytic material (In@CeO 2 ).
[0076] The samples of Examples 1-4 are taken as examples to characterize them and conduct propane dehydrogenation catalytic tests.
[0077] When conducting propane dehydrogenation catalytic tests, the following method is used to conduct propane dehydrogenation catalytic experiments:
[0078] 300 mg of the metal particle / porous metal oxide composite catalytic material prepared in the above Examples 1-4 and 300 mg of 40-60 mesh quartz sand were mechanically mixed and uniformly loaded into a fixed bed reactor containing a quartz tube with a diameter of 8 mm, and the temperature was raised to 600° C. for 1 h in a nitrogen atmosphere (flow rate: 20 mL / min), and a mixed gas of propane, carbon dioxide, and argon was introduced for reaction, wherein the flow rates of propane, carbon dioxide, and argon were 5, 5, and 15 mL / min, respectively.
[0079] Figure 1For Ni@Al in Example 1 2 O 3 TEM images and element distribution diagrams at different magnifications: Figure 1 a is Ni@Al 2 O 3 High-angle annular dark-field transmission electron microscopy (HAADFTEM) images and Al, O, and Ni element distribution maps, Figure 1 b is Ni@Al 2 O 3 High-resolution TEM image of . Figure 1 The distribution positions of Al and O elements in a are almost the same, indicating that Al 2 O 3 Successful synthesis, the distribution diagram of Ni element shows that Ni particles are in Al 2 O 3 The dispersion is higher. Figure 1 b shows that the Ni particles are similar in size and 2 O 3 Evenly distributed on the substrate.
[0080] Figure 2 V@Al in Example 2 2 O 3 TEM images and element distribution diagrams at different magnifications: Figure 2 a is V@Al 2 O 3 High-angle annular dark-field transmission electron microscopy (HAADFTEM) images and Al, O, and V element distribution diagrams. Figure 2 b is V@Al 2 O 3 High-resolution TEM image of . Figure 2 The results show that V element in Al 2 O 3 Evenly distributed on the substrate.
[0081] Figure 3 Cr@Al in Example 3 2 O 3 TEM images and element distribution diagrams at different magnifications: Figure 3 a is Cr@Al 2 O 3 High-angle annular dark-field transmission electron microscopy (HAADFTEM) images and Al, O, and Cr element distribution maps. Figure 3 b is Cr@Al 2 O 3 High-resolution TEM image of . Figure 3 The results show that Cr particles 2 O 3 Highly dispersed and evenly distributed on the matrix.
[0082] Figure 4 In@CeO in Example 4 2 TEM images and element distribution diagrams at different magnifications: Figure 4 a is In@CeO 2 High-angle annular dark-field transmission electron microscopy (HAADFTEM) images and distribution diagrams of Ce, O, and In elements. Figure 4 b is In@CeO 2 High-resolution TEM image of . Figure 4 The results show that In metal particles are 2 The particles are evenly distributed on the matrix with high dispersion.
[0083] Figure 5 For Ni@Al in Examples 1-4 2 O 3 、V@Al 2 O 3 ,Cr@Al 2 O 3 、In@CeO 2 Propane dehydrogenation performance curve. Figure 5 a is Ni@Al 2 O 3 The propane dehydrogenation performance curves show the initial propane conversion, propylene selectivity and CO 2 The conversion rates were 21.55%, 87.45%, and 12.43% respectively; Figure 5 b is V@Al 2 O 3 The propane dehydrogenation performance curves show the initial propane conversion, propylene selectivity and CO 2 The conversion rates were 24.02%, 85.71%, and 24.55% respectively; Figure 5 c is Cr@Al 2 O 3 Propane dehydrogenation performance curve, its initial propane conversion, propylene selectivity and CO 2 The conversion rates were 17.73%, 82.05%, and 21.33% respectively; Figure 5 d is Cr@Al 2 O 3 The propane dehydrogenation performance curves show the initial propane conversion, propylene selectivity and CO 2 The conversion rates were 14.81%, 74.32% and 29.79% respectively. Figure 5 The results show that the composite material synthesized by implanting metal particles prepared by laser irradiation technology into porous metal oxides using the complex precipitation method has high catalytic activity and stability, which is beneficial to prove the efficiency and feasibility of the present invention.
[0084] It should be noted that, in this article, terms such as "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0085] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A metal particle / porous active metal oxide composite catalytic material, characterized in that: The metal particles are uniformly loaded on the surface and in the matrix of the porous active metal oxide, and the metal particles are in a highly dispersed state.
2. A method for preparing a metal particle / porous active metal oxide composite catalytic material, characterized in that: The method comprises the following steps: Step 1: preparing a colloidal solution of metal particles by liquid phase pulsed laser irradiation technology; Step 2: Under magnetic stirring, dissolving the precursor metal salt for preparing the porous active metal oxide in the metal particle colloidal solution in step 1, adding ammonium carbonate as a precipitant, and uniformly dispersing by ultrasonication to obtain a mixed solution; Step 3: placing the mixed solution of step 2 in a constant temperature oven, keeping the temperature, using a complex precipitation method to react ammonium carbonate with metal salt ions to generate a complex precipitate, then centrifugally separating and washing the precipitate, and drying overnight to obtain a solid intermediate product; Step 4: Place the solid intermediate product obtained in step 3 into a muffle furnace and perform high-temperature calcination treatment to finally obtain a metal particle / porous active metal oxide composite catalytic material.
3. The method for preparing the metal particle / porous active metal oxide composite catalytic material according to claim 2, characterized in that: Step 1 specifically includes: A metal target is selected, polished and placed in a solvent, the condensation temperature is maintained at -20-0°C, a nanosecond pulse laser beam is used to bombard the metal target, and ultrasonic treatment is performed at the same time. After irradiation for a certain period of time, the metal target is taken out to obtain a metal particle colloidal solution.
4. The method for preparing the metal particle / porous active metal oxide composite catalytic material according to claim 3, characterized in that: In step 1, the metal target used in the preparation of the metal particle colloidal solution is one or more of In, V, Cr, and Ni; and / or the solvent used is ultrapure water, and / or the laser flux of the pulsed laser beam is 600-2000 mJ pulse -1 cm -1 The laser beam irradiates the metal target for 2-15 min.
5. The method for preparing the metal particle / porous active metal oxide composite catalytic material according to claim 2, characterized in that: The porous metal oxide is one or more of aluminum oxide, cerium oxide, gallium oxide and zirconium oxide; wherein the precursor metal salt is one or more of aluminum nitrate, aluminum sulfate, aluminum chloride, cerium nitrate, cerium sulfate, cerium chloride, gallium nitrate, gallium acetate, gallium chloride, zirconium nitrate, zirconium chloride and zirconium sulfate; the molar ratio of ammonium carbonate to metal salt is 2:1-9:
1.
6. The method for preparing the metal particle / porous active metal oxide composite catalytic material according to claim 2, characterized in that: In step 2, the ratio of the metal salt to the metal particle colloidal solution is 0.02 mol / L to 0.20 mol / L; the time of the magnetic stirring and ultrasonic dispersion treatment is 15 min and 30 min, respectively.
7. The method for preparing the metal particle / porous active metal oxide composite catalytic material according to claim 2, characterized in that: In step 3, the insulation temperature is 80-180°C, the insulation time is 6-36 h, and the centrifugation is performed at a speed of 7000 r / min for 3 min; when washing the precipitate, it is washed three times with ultrapure water and anhydrous ethanol respectively; and the drying temperature is 60°C.
8. The method for preparing the metal particle / porous active metal oxide composite catalytic material according to claim 2, characterized in that: In step 4, the calcination temperature is 500-900°C, the heating rate is 10°C / min, and the holding time is 3-5 h.
9. Use of the metal particle / porous active metal oxide composite catalytic material according to claim 1 or the metal particle / porous active metal oxide composite catalytic material prepared by the method according to any one of claims 2 to 8 in propane dehydrogenation.
10. Use of the metal particle / porous active metal oxide composite catalytic material in propane dehydrogenation as claimed in claim 9, characterized in that: The metal particles / porous metal oxide composite catalytic material and quartz sand are mixed evenly, loaded into a fixed bed reactor containing a quartz tube, and a mixed gas of propane, carbon dioxide and argon is introduced in a nitrogen atmosphere to carry out a dehydrogenation reaction.